Synthesis of 4-(5-Benzyl-2-phenylpyrimidin-4-yl)morpholines as Novel PI3K Inhibitors Via Acetates of Baylis-Hillman Adducts and Benzamidines - Yang, Chunhao; Yu, Haofei; Yang, Na; Meng, Linghua; Xu, Jing; Zhang, Rongping; Xie, Yuyuan; Ding, Jian (Letters in Organic Chemistry, 2009)
The key intermediates 5-benzyl-2-phenylpyrimidin-4(3H)-ones or (E)-5-benzylidene-2-phenyl- 5,6-dihydropyrimidin- 4(3H)-ones were obtained conveniently by cyclization of the acetates of Baylis-Hillman adducts and benzamidine hydrochloride in the presence of sodium ethoxide at room temperature. Chlorination of pyrimidinones with phosphorus oxychloride and subsequent treatment with morpholine and demethylation yielded PI3K inhibitors.
Keywords: dihydropyrimidin-4(3H)-one